Implementasi Pembelajaran STEM pada Materi Ekosistem terhadap Kemampuan Berpikir Kritis Peserta Didik - Aufa Yasifa; Nurul Hidayah Hasibuan; Putri Akhiriyani Siregar; Sinta Zakiyah; Nirwana Anas (Journal on Education, 2023)
Implementation of STEM Learning in Ecosystem Material on Students' Critical Thinking Ability. STEM is a modern approach that integrates STEM aspects to develop students' skills in solving problems that arise in 21st century life. This study aims to obtain an overview of students' critical thinking skills. The sample of this study was students of class Vb UPT SD Negeri 064037 Medan for the 2022/2023 Academic Year. The type of research used in this research is the Pre-Experimental Design with the One Group Pretest-Posttest Design. Data on students' thinking skills were collected using a critical thinking ability test instrument. The results showed that the average value of N-Gain in the Vb class was 0.81 which was in the high category.